Pakistan : Staff Report for the 2002 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility Arrangement, and Request for Waivers of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
The economic outlook remains clouded by regional and domestic security concerns. Real GDP growth and inflation were broadly in line with program projections in 2001-02. The balance of payments position unproved faster than expected. The budget deficit target for 2001-02 (as set during the first review) was met, despite a shortfall in the Central Board of Revenue (CBR). Broad money increased strongly in 2001-02, despite efforts to sterilize foreign exchange inflows. Reforms in the financial sector made significant progress.